Ultrahigh field and ultrahigh resolution fMRI. (June 2021) - Uğurbil, Kamil
Abstract: Functional magnetic resonance imaging (fMRI) has become one of the most powerful tools for investigating the human brain. The development of 7 Tesla has played a critical role in this evolution by enabling higher resolution and more accurate functional maps. However, even with these gains, the fMRI approach is challenged relative to the spatial scale over which brain function is organized. Therefore, going forward, significant advances in fMRI are still needed. Such advances will predominantly come from magnetic fields significantly higher than 7 Tesla, which is the most commonly used ultrahigh magnetic field platform today, and additional technologies that will include developments predominantly in RF coil technologies, image reconstruction, noise suppression, and image analysis to further enhance and augment the gains that can be realized by going to higher magnetic fields.